2015
DOI: 10.1371/journal.pone.0119770
|View full text |Cite
|
Sign up to set email alerts
|

Phytase Modulates Ileal Microbiota and Enhances Growth Performance of the Broiler Chickens

Abstract: Phytase is well studied and explored, however, little is known about its effects on the microbial ecology of the gastrointestinal tract. In total, 400 one-day-old female Ross 308 chicks were randomly distributed to four experimental groups. The dietary treatments were arranged as a 2 × 2 complete factorial design, with the factors being adequate (PC) or insufficient calcium (Ca) and digestible phosphor (dP)(NC) and with or without 5000 phytase units (FTU)/kg of Escherichia coli 6-phytase. The gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 41 publications
7
78
1
2
Order By: Relevance
“…In this study, a higher frequency of bacteria belonging to the Lactobacillus genera were also found in the ileum of hens fed a diet enriched with F. In addition, bacteria belonging to the Turicibacter genera were observed. Similar results were seen by Ptak et al (2015), where 6-phytase also increased Lactobacillus sp. and Enterococcus sp.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, a higher frequency of bacteria belonging to the Lactobacillus genera were also found in the ileum of hens fed a diet enriched with F. In addition, bacteria belonging to the Turicibacter genera were observed. Similar results were seen by Ptak et al (2015), where 6-phytase also increased Lactobacillus sp. and Enterococcus sp.…”
Section: Discussionsupporting
confidence: 84%
“…Digesta samples belonging to diets C and H, that were both supplemented with Ca, were significantly different from samples derived from Ca-free diets E and F ( p < 0.05; Table S4). It is known that higher doses of Ca in the diets can lead to an increase of the pH (Ptak et al, 2015) and low precaecal P digestibility (Adeola and Walk, 2013; Hamdi et al, 2015), which could possibly influence the presence or absence of some OTUs. An effect of P supplementation was observed in the microbial communities of the ileum mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…In consequence, the amount of calcium (Ca) and P required in diet formulation can be reduced following release of these two elements from phytate complexes (Zeller et al, 2015). Changes in Ca and P supplementation affected the composition and activity of the microbial community in the digestive tract of broilers (Ptak et al, 2015). Because the microbes are involved to a variable extent in enzymatic hydrolysis of nutrient fractions in the digestive tract, it is necessary to understand the role of the microbial community of the gut (Eeckhaut et al, 2011) and its interaction with the host, in order improve the utilization of nutrients such as phytate bound P by the bird.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, more than 900 bacterial species have been identified, and it is well documented that the disturbance of microbial homeostasis can have significant negative effects on intestinal health and bird performance (Stanley et al, 2014). In the current experiments, the analysed microbiota populations were chosen as gut health indicators on the basis of our earlier research (Józefiak et al, 2011(Józefiak et al, , 2012(Józefiak et al, , 2013Ptak et al, 2015;Kierończyk et al, 2016;Dunislawska et al, 2017). Although it cannot be demonstrated that final performance indices of the birds are improved due to supplementation with insect meals, significant changes in microbiota populations were marked.…”
Section: Discussionmentioning
confidence: 99%